Attrition of HIV‐exposed infants from early infant diagnosis services in low‐ and middle‐income countries: a systematic review and meta‐analysis. Issue 11 (22nd November 2018) - Carlucci, James G; Liu, Yu; Friedman, Halle; Pelayo, Brenda E; Robelin, Kimberly; Sheldon, Emily K; Clouse, Kate; Vermund, Sten H
Abstract: Introduction: Identification and retention of HIV‐exposed infants in early infant diagnosis (EID) services helps to ensure optimal health outcomes. This systematic review and meta‐analysis examines the magnitude of attrition from EID services in low‐ and middle‐income countries (LMICs). Methods: We performed a comprehensive database search through April 2016. We included original studies reporting retention/attrition data for HIV‐exposed infants in LMICs. Outcomes included loss to follow‐up (LTFU), death and overall attrition (LTFU + death) at time points along the continuum of EID services. At least two authors determined study eligibility, performed data extraction and made quality assessments. We used random‐effects meta‐analytic methods to aggregate effect sizes and perform meta‐regression analyses. This study adhered to PRISMA reporting guidelines. Results: We identified 3040 unique studies, of which 92 met eligibility criteria and were included in the quantitative synthesis. The included studies represent data from 110, 805 HIV‐exposed infants, the majority of whom were from Africa (77%). LTFU definitions varied widely, and there was significant variability in outcomes across studies. The bulk of attrition occurred in the first six months of follow‐up, with additional losses over time. Overall, 39% of HIV‐exposed infants were no longer in care at 18 months. When restricted to non‐intervention studies, 43% were not retained at 18 months. Conclusions: These findings underscore the high attrition of HIV‐exposed infants from EID services in LMICs and the urgent need for implementation research and resources to improve retention among this vulnerable population.